1987
DOI: 10.1007/bf00915552
|View full text |Cite
|
Sign up to set email alerts
|

Patients with condyloma acuminatum exhibit decreased interleukin-2 and interferon gamma production and depressed natural killer activity

Abstract: Peripheral blood mononuclear cells were obtained from 20 untreated condyloma acuminatum patients and from an equal number of sex- and age-matched controls and assayed for cell surface antigen expression, natural killer activity, and lymphokine production. Patient peripheral blood mononuclear cells had significantly lower helper-to-suppressor T-cell ratios (Leu3/Leu2) (P less than 0.05) and significantly higher percentages of Leu 2+ Tac+ cells (activated suppressor/cytotoxic cells) (P less than 0.05) and Leu 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…It is not clear so far whether this local depletion is the cause or the result of viral infection. In the peripheral blood of patients with condvlomata, higher percentages of suppressor/cytotoxic T cells (CDS), lower percentages of helper/inducer T cells (CD4) and a lower helper (CD4)/suppressor (CD8) T-cell ratio are described [41,42], Otherwise, immunosuppressed pa tients have an increased risk for HPV infection and cervi cal neoplasia [43]. The normal Langerhans' cell counts in CIN 2 and 3 in our study may reflect activated antigen presentation in contrast to depressed function in CIN 1.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear so far whether this local depletion is the cause or the result of viral infection. In the peripheral blood of patients with condvlomata, higher percentages of suppressor/cytotoxic T cells (CDS), lower percentages of helper/inducer T cells (CD4) and a lower helper (CD4)/suppressor (CD8) T-cell ratio are described [41,42], Otherwise, immunosuppressed pa tients have an increased risk for HPV infection and cervi cal neoplasia [43]. The normal Langerhans' cell counts in CIN 2 and 3 in our study may reflect activated antigen presentation in contrast to depressed function in CIN 1.…”
Section: Discussionmentioning
confidence: 99%
“…Schafer et al [8] showed a tenfold increase in the relative risk to developing cervical neoplasia in HIV-infected women with respect to outpa tient population. Similarly, Carlson et al [12] and Cauda et al [ 13] observed a decrease of cellular immune reactivi ty in women with genital HPV infection-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In regressing skin warts, mononuclear cell inflammatory infiltrates containing macrophages, T lym phocytes, and natural killer (NK) cells are the major mor phological feature [76][77][78], This reaction has a biphasic course in the cottontail rabbit papillomavirus (CRPV) model: infiltrates consist of polymorphonuclear cells dur ing the early stage and are replaced by predominantly perivascular cell infiltrates composed of mononuclear cells in the later stage of the local immune response [79]. Cellular immune impairment is associated with condylo ma acuminatum in humans since T helper cells are depleted and the T4:T8 ratio is reversed in tissue and peripheral blood [80,81]. The number of Langerhans cells is decreased in cervical-HPV-associated lesions [82][83][84][85], but these Langerhans cells show a higher expression of major histocompatibility complex (MHC) class II antigen [83], Recognition of HPV-16-infected kératinocytes by NK cells depends on persistence of the lesion and cannot be corrected by incubation of peripheral blood mononu clear cells (PBMCs) with interferon-y and/or interleukin-2, although these cytokines are decreased in condylomata [81.…”
Section: Course Of Infectionmentioning
confidence: 99%